Patient and caregiver experiences at a Multidisciplinary Tracheostomy Clinic. (October 2020) - Ali, Syed Omar; Yeung, Tatiana; McKeon, Mallory; Maddock, Meaghan; Graham, Robert J.; Nuss, Roger; Rahbar, Reza; Watters, Karen
Abstract: Introduction: Children with tracheostomy are a heterogeneous population requiring care from multiple specialties. Multidisciplinary approaches to treating such patients helps to improve the quality of care they receive. Our institution established a Multidisciplinary Tracheostomy Clinics (MDTC) to address outpatient care coordination for tracheostomy patients by providing care from multiple disciplines at a single visit. We report patient/caregivers' experiences of our MDTC. Methods: Patients with tracheostomy or their caregivers were prospectively recruited between Dec 2017–Oct 2019 to complete surveys assessing their experience at the MDTC. Demographic and satisfaction questionnaires were sent electronically by a REDCap survey distribution tool. Demographic data were collected, such as patient's residence and education level. Medical care variables assessed included history of MDTC attendance, commute time, medical specialties seen, tracheostomy "Go-Bag" use, home-care nursing, and MDTC satisfaction ratings. Results: Twenty-nine patients/caregivers completed the satisfaction survey and 22 completed both the satisfaction survey and demographics questionnaire. Patient ages ranged from 11 months to 36 years. Twenty-three (79%) participants commuted for up to 2 h to the MDTC, and 6 (21%) commuted for more than 2 h. The median number of medical specialties seen at the MDTC was 3. All participants were satisfied that they saw all requested specialties. Tracheostomy supplies were checked for 25 of 28 patients. Twenty-three of 28 subjects rated staff teamwork as "excellent." Twenty-four of 28 patients were "highly likely" to recommend the MDTC. Twenty-three of 28 participants were "highly likely" to return, and 4 were "somewhat likely" to return. Conclusion: This study demonstrates that patients with tracheostomy and caregivers were satisfied with the improved coordination and facilitation of care through a Multidisciplinary Tracheostomy Clinic.